Frecuency of carbapenemase-producing enterobacteriaceae in anal swabs from an adult unit intensive care - Vallejos, Augusto Joaquín (2021)
Fil: Vallejos, Augusto Joaquín. Hospital Dr. Julio C. Perrando. Servicio de Microbiología Clínica; Argentina.